Blow Up for a Quasilinear Schrodinger Equationi in Nonisotropic Spaces (Journal of Partial Differential Equations, 2020)
Consider the blow up results for local smooth solutions of a quasilinear Schrödinger equation iu_t + Δu + β|u|^{p-2}u + θ(Δ|u|²)u = 0, u|_{t=0} = u_0(x), x ∈ \mathbb{R}^N in nonisotropic space.
Keywords: Blow up; quasilinear Schrödinger equation